Doing harm : the truth about how bad medicine and lazy science leave women dismissed, misdiagnosed, and sick - Dusenbery, Maya (HarperOne, an imprint of HarperCollinsPublishers, 2018)
"In this shocking, hard-hitting expose in the tradition of Naomi Klein and Barbara Ehrenreich, the editorial director of Feministing.com, reveals how gender bias infects every level of medicine and healthcare today--leading to inadequate, inappropriate, and even dangerous treatment that threatens women's lives and well-being. Modern medicine is failing women. Half of all American women suffer from at least one chronic health condition--from autoimmune disorders and asthma to depression and Alzheimer's disease--and the numbers are increasing. A wealth of research has revealed that women often exhibit different symptoms than their male counterparts, suffer disproportionately from many debilitating conditions, and may react differently to prescription drugs and other therapies. Yet more than twenty years after the law decreed that women be included in all health-related research and drug development, doctors are still operating with a lingering knowledge gap when it comes to women's health. And they're not immune to unconscious biases and stereotypes that can undermine the doctor-patient relationship. The consequences can be catastrophic: Too often, women are misdiagnosed, poorly treated, and find their complaints dismissed as "just stress" or "all in your head." Meanwhile, they're getting sicker. Maya Dusenbery brings together scientific and sociological research, interviews with experts within and outside the medical establishment, and personal stories from regular women to provide the first comprehensive, accessible look at how sexism in medicine harms women today. In addition to offering a clear-eyed explanation of the root causes of this insidious and entrenched bias and laying out its effects, she suggests concrete steps we can take to cure it. Eye-opening and long-overdue, Doing Harm is an empowering call to action for health care providers and all women"--